Mitochondria as a Target for the Cardioprotective Effects of Cydonia oblonga Mill. and Ficus carica L. in Doxorubicin-Induced Cardiotoxicity - Gholami, Saman; Hosseini, Mir-Jamal; Jafari, Leila; Omidvar, Fatemeh; Kamalinejad, Mohammad; Mashayekhi, Vida; Hosseini, Seyed Hojjat; Kardan, Azin; Pourahmad, Jalal; Eskandari, Mohammad Reza (Drug Research, 2017)
Quince (Cydonia oblonga Mill.) and fig (Ficus carica L.) exhibit a broad spectrum of pharmacological activities. Regarding the cardiotoxic effect of doxorubicin (DOX) is mediated mainly through mitochondrial oxidative stress and dysfunction; the present study evaluated the cardioprotective effects of the aqueous extracts of Cydonia oblonga Mill. fruit (ACO) and Ficus carica L. fruit (AFC) against DOX-induced cardiotoxicity. Cardiomyocytes toxicity was induced in male Sprague Dawley rats by intraperitoneal (ip) injections of 2.5 mg/kg DOX 3 times per week for a period of 2 weeks. After heart failure was induced in the rats, the animals were decapitated and their hearts were immediately removed. Then, the cardiac mitochondria were isolated by differential ultracentrifugation, and the protective effects of each particular extract on mitochondrial oxidative stress and dysfunction were determined. ACO and AFC ameliorated mitochondrial dysfunction in the isolated mitochondria and prevented mitochondrial reactive oxygen species formation, membrane lipid peroxidation, mitochondrial swelling, mitochondrial membrane potential collapse (%ΔΨm), and cytochrome c release. Also, the extracts significantly increased reduced glutathione levels and succinate dehydrogenase activity. These results indicated that ACO and AFC have beneficial effects against DOX cardiotoxicity which mediated by attenuating mitochondrial dysfunction. Therefore, it can be suggested that quince and fig may increase the therapeutic index of DOX.
Keywords: C. oblonga Mill.; F. carica L.; quince; fig; heart failure; cardiotonic